Kontribusi latar belakang sosial ekonomi orang tua di masa Covid-19 terhadap perkembangan sains anak (survei pada anak taman kanak-kanak di Kecamatan Bukik Barisan) - Khairiah, Fisna; Eliza, Delfi (Jurnal Aplikasi IPTEK Indonesia, 2021)
Education is one of those affected by Covid-19, so students carry out the learning process from home and the role of parents is demanded more so that they can develop science in children. The socioeconomic status of parents is very important in supporting facilities for learning and developing children's science. This study aims to describe the contribution of parents' socioeconomic background during the Covid-19 period to children's scientific development. This study uses a descriptive correlational quantitative method with 94 respondents as parents of children in Kindergarten, Bukik Barisan District. Data analysis was performed using the regression method using dummy variables with SPSS 26 software. The instrument was validated using expert judgment techniques and the reliability test showed Cronbach's Alpha 0.872. The research findings show that learning outcomes based on (1) parental occupation and income are in the good category, (2) the contribution of parents' work to the development of science is 3.7%, (3) the contribution of parents' income to the development of science is 9.3%, (4) the contribution of work and income of parents to the development of science is 14.7%, (5) overall, work and income contribute to the development of children's science.